The role of unethical behavior in moderating the influence of governance, risk management, and compliance on financial fraud prevention in Indonesian local governments / Otniel Safkaur ... [et al.] - Safkaur, Otniel; Tarjo, Tarjo; Anggono, Alexander; Mohd Sanusi, Zuraidah (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
This study examined the moderation effect of unethical behavior on the relationship of governance, risk management, and compliance on financial fraud prevention in the context of Indonesian Local Governments. Focusing on Regional Apparatus Organizations and local government auditor offices, the research comprised of a robust sample of 120 respondents. Employing the rigorous Structural Equation Modeling-Partial Least Square (SEM-PLS) with WarpPLS software for analysis, the findings revealed a significant weakening effect of unethical behavior on the relationship between governance, risk management, and compliance and financial fraud prevention in the local government setting. Notably, this research contributes to the limited literature on governance, risk management and compliance in the realm of local government studies. Moreover, by incorporating a moderating variable, this study enhances its academic significance, as it addresses the pervasive issue of unethical conduct that permeates the local government landscape and further engages with prior debates in the field.